Exploring the Antifungal Activity and Action of Saussurea costus Root Extracts against Candida albicans and Non-albicans Species - Melad F. Soliman; Youssria M. Shetaia; Ahmed A. Tayel; Alaa M. Munshi; Fuad A. Alatawi; Mohammed A. Alsieni; Mahmoud A. Al-Saman (Antibiotics, 2022)
The isolation and assessment of the active constituents in polar and non-polar crude extracts of Saussurea costus roots as antifungal agents, against Candida albicans and non-C. albicans (NAC) species, was the aim of this current investigation. The SEM “Scanning electron microscopy” imaging provided potential action modes of n-hexane extract (nhhE) toward Candida spp., whereas the TLC-DB “Thin layer chromatography-direct bioautography” was employed for detecting the anticandidal compounds. nhhE had the greatest biocidal activity against all strains and clinical isolates of Candida spp. with maximum zones of inhibition. SEM revealed the occurrence of irregular, dense inclusions of C. albicans cell walls after treatment with nhhE for 12 h. Complete morphological distortions with lysed membranes and deterioration signs appeared in most treated cells of C. parapsilosis. The most effectual compound with anticandidal activity was isolated using TLC-BD and identified as sesquiterpene by GC/MS analysis. The infra-red analysis revealed the presence of lactone ring stretching vibrations at 1766.72 cm−1. The anticandidal activity of nhhE of S. costus roots was confirmed from the results, and the treated cotton fabrics with nhhE of S. costus possessed observable activity against C. albicans. Data could recommend the practical usage of S. costus extracts, particularly nhhE, as influential natural bioactive sources for combating pathogenic Candida spp.